A presença/ausência negra em escolas da região de Sorocaba e o impacto na formação da identidade das crianças do ensino fundamental anos iniciais - Bueno, Gabrielle Christina Bento (Universidade Federal de São Carlos, 2021)
This course conclusion work (TCC) presents data that lead us to reflect on the historical and structural differences, which lead to the presence/absence of black people in different spaces, specifically addressed here within the school environment, in the early years of the elementary School. The following question was taken as a research problem, the results of which are presented here: what has been the impact that the black presence/absence in schools in the region of Sorocaba has had on the process of building the identity of children in elementary school in the initials? In the search for an answer to the research question, a bibliographic and documentary research was developed, with a qualitative bias. The objective was to get to know the scenario of these schools, particularly in relation to black presence/absence and how this has affected the construction of children's identity. Thus constituted, this TCC, at first, addresses the concept of identity and black identity. Afterwards, the presence of black people in Brazilian society is discussed, as well as in the city of Sorocaba, specifically dealing with this problem in public and private schools. At the end of the text, an analysis is presented on the construction of the identity of the black people based on the document Pedagogical Political Project, restricted to private and public schools in Sorocaba, with a cut made from schools that this researcher has already worked on.
The black presence/absence in schools in the region of Sorocaba and the impact on the education of the identity of children from elementary school to early years
Keywords: Educação; Ensino Fundamental; Identidade; Relações Étnico-raciais; RMS (Região Metropolitana de Sorocaba); Education; Elementary School; Ethnic-Racial Relations; RMS (Metropolitan Region of Sorocaba); CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO